A influência dos fatores bióticos e abióticos no néctar coletado por Melipona subnitida (APIDAE, MELIPONINI) na caatinga - Limão, Amanda Aparecida de Castro (2015)
Biotic and abiotic factors are constantly influencing the foraging bees. Evaluate this influence is a manner to understand the ecology of these organisms within their environment. Unpredictable environments such as Brazilian tropical dry-forest, the Caatinga, represents a challenge for the bees, once the combination of extended periods with little funding and extreme weather conditions, makes the survival of bees difficult. In this study, we investigated the foraging nectar of stingless bee Melipona subnitida within their natural habitat, Caatinga. The experiments were conducted in the city of Mossoró/RN, Brazil. The findings show that bees M. subnitida has an active annual foraging despite behavioral changes and that these changes are influenced by factors temperature, relative humidity, rainfall and amount of available floral resources. M. subnitida presents strategies to survive the environmental conditions of the region, especially climate. In addition to the diluted nectar collected during hot and dry periods, there was the first time for this specie collection of water. Key words: Stingless bees, semiarid region, sugar, water foraging